REDUCTION OF PREOPERATIVE FASTING IN PATIENTS UNDERGOING ELECTIVE CARDIAC SURGERY - Siebert Lobão, Phannia Olimpia; Lopes Silva, Jackelyne; Folador Frederico, Rafael; Nascimento Ronchi, Silas; Chiepe, Letícia; Spalenza da Silva, Bruno; Lima Garcez, Michelle; Bellettini-Santos, Tatiani (UNESC em Revista, 2025)
Prolonged fasting in the preoperative period of elective cardiac surgeries causes metabolic changes, such as increased insulin resistance, infections, discomfort, and more extended hospital stays, resulting in high public health costs. The objective of this study was to evaluate the preoperative fasting abbreviation protocol, introduced in April 2023, and compare it to conventional fasting. This is a retrospective analytical study conducted in a hospital in the northwest region of Espírito Santo, utilizing data collection from electronic medical records and the institutional database, which were subsequently analyzed using SPSS software, version 21.0. Patients undergoing elective cardiac surgery 8 months before the protocol, subject to conventional fasting of at least 8 hours, were included, compared to those who adopted the fasting abbreviation in the 8 months following the implementation of the protocol, with suspension of solid food 6 hours before surgery and restricted liquid diet 3 hours before. There was no difference in the length of Intensive Care Unit (ICU) stay or mortality between the groups. Regarding glycemic variation, there was an increase in glycemic levels in the fasting abbreviation group compared to the conventional fasting group [F(157) = 0.155, p<0.01], with a small effect size of the difference (Cohen’s d = 0.3902). The glycemic increase is demonstrated to have low clinical relevance, and further studies, including randomized clinical trials, are needed to better understand the variables involved in fasting abbreviation in cardiac surgeries and to optimize health services. Keywords: Fasting abbreviation, Cardiac surgery, Hyperglycemia, Glycemic control, Perioperative.